Physiological determinants of Yo-Yo intermittent recovery tests in male soccer players - Rampinini, E.; Sassi, A.; Azzalin, A.; Castagna, C.; Menaspà, P.; Carlomagno, D.; Impellizzeri, F. M. (European Journal of Applied Physiology, 2010)
The physiological determinants of performance in two Yo-Yo intermittent recovery tests (Yo-YoIR1 and Yo-YoIR2) were examined in 25 professional (n = 13) and amateur (n = 12) soccer players. The aims of the study were (1) to examine the differences in physiological responses to Yo-YoIR1 and Yo-YoIR2, (2) to determine the relationship between the aerobic and physiological responses to standardized high-intensity intermittent exercise (HIT) and Yo-Yo performance, and (3) to investigate the differences between professional and amateur players in performance and responses to these tests. All players performed six tests: two versions of the Yo-Yo tests, a test for the determination of maximum oxygen uptake ( [(\textV)\dot]\textO2 max VO2max), a double test to determine [(\textV)\dot]\textO2 VO2kinetics and a HIT evaluation during which several physiological responses were measured. The anaerobic contribution was greatest during Yo-YoIR2. [(\textV)\dot]\textO2 max VO2maxwas strongly correlated with Yo-YoIR1 (r = 0.74) but only moderately related to Yo-YoIR2 (r = 0.47). The time constant (t) of [(\textV)\dot]\textO2 VO2kinetics was largely related to both Yo-Yo tests (Yo-YoIR1: r = 0.60 and Yo-YoIR2: r = 0.65). The relationships between physiological variables measured during HIT (blood La-, H+, HCO3 - and the rate of La- accumulation) and Yo-Yo performance (in both versions) were very large (r > 0.70). The physiological responses to HIT and the t of the [(\textV)\dot]\textO2 VO2kinetics were significantly different between professional and amateur soccer players, whilst [(\textV)\dot]\textO2 max VO2maxwas not significantly different between the two groups. In conclusion, [(\textV)\dot]\textO2 max VO2maxis more important for Yo-YoIR1 performance, whilst t of the [(\textV)\dot]\textO2 VO2kinetics and the ability to maintain acid-base balance are important physiological factors for both Yo-Yo tests.